Analisis Kelayakan Pendirian Pusat Distribusi Provinsi (PDP) Jawa Barat - Eka Setiajatnika; Trida Gunadi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this study was to analyze the feasibility of establishing a Provincial Distribution Center (PDP) in Purwakarta Regency, West Java which was assessed from the aspects of the Potential of Production Centers and Commodity Demand, Infrastructure, Socio-Economic Conditions, Environmental Conditions, Regional Spatial Plans, Regulations, Land and Actors. Distribution / Logistics Services. This research used Pairwise Comparison Matrix method. It was concluded that, Purwakarta Regency was deemed appropriate and sufficient in determining the criteria as a Provincial Distribution Center.